An international, cross-sectional survey of the management of Vancouver type B1 periprosthetic femoral fractures around total hip arthroplasties. Issue 2 (February 2018) - Bates, Brent D.; Walmsley, David W.; Vicente, Milena R.; Kuzyk, Paul R.; Nauth, Aaron; Waddell, James P.; McKee, Michael D.; Schemitsch, Emil H.
Abstract: Introduction: The incidence of periprosthetic femoral fractures around total hip arthroplasties is increasing. Fractures around a stable implant stem (Vancouver type B1) are among the most common of these fractures. Various fixation strategies for Vancouver type B1 periprosthetic fractures have been reported in the literature; however, little high-level evidence exists. This study was designed to determine the current management strategies and opinions among orthopaedic surgeons treating Vancouver type B1 periprosthetic femoral fractures, and to evaluate the need for a large prospective randomized controlled trial for the management of these injuries. Methods: Orthopaedic surgeon members of the Orthopaedic Trauma Association (OTA), the Canadian Orthopaedic Association (COA), and the Hip Society were invited to participate in a 51-item web-based survey surrounding the management of periprosthetic femoral fractures around total hip replacements, as well as the perceived need for future research in this area. Responses were summarized using proportions, and further stratified by practice type, case volume, surgeon age, and fellowship training. Results: For Vancouver type B1 fractures, open reduction and internal fixation (ORIF) with locked plating was favoured slightly over ORIF with cable plating ± cortical strut allograft (51.1% versus 45.5%). When compared to cable plating with cortical strut allograft, respondents believed that isolated locked plating resulted in lower nonunion and reoperation rates, but similar infection and malunion rates. Subgroup analyses revealed that practice type, surgeon age, case volume, and fellowship training influenced surgeons' management of periprosthetic femoral fractures and beliefs regarding complications. There is high demand for a large prospective randomized controlled trial for Vancouver type B1 fracture fixation. Conclusions: Consensus surrounding the management of Vancouver type B1 periprosthetic femoral fractures is lacking, and there is a perceived need among orthopaedic surgeons for a large prospective randomized controlled trial in order to define the optimal management of these injuries.